PENGARUH PERSEPSI KEAMANAN TERHADAP LOYALITAS PENGGUNA E-BANKING DENGAN KEPERCAYAAN (TRUST) SEBAGAI VARIABEL INTERVENING - Wardani, Dewi Kusuma; Fahlefi, Azka Redo (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to determine the effect of perceived security on the loyalty of e-banking users through trust as an intervening variable. The population in this study is BNI bank customers who use e-banking services with a total sample of 104 respondents. The data collection method in this study used the snowball sampling method. Data was collected by distributing questionnaires in the form of google form to respondents through social media. The data analysis used in this research is path analysis which is processed using the IBM SPSS version 20 tool. The results of this study indicate that the perception of security has a positive effect on trust. Perceptions of security and trust do not affect the loyalty of e-banking users. The perception of security has no effect on the loyalty of e-banking users through trust.